Ultrasonography-Guided Perineural Injection of the Ramus ventralis of the 7 and 8th Cervical Nerves in Horses: A Cadaveric Descriptive Pilot Study - Touzot-Jourde, Gwenola; Geffroy, Olivier; Tallaj, Amélie; Gauthier, Olivier; Denoix, Jean-Marie (Frontiers in Veterinary Science, 2020)
Objective: To describe the feasibility and dye diffusion of selective perineural injection of the 7th and 8th cervical nerve (C7 and C8) ramus ventralis under ultrasonographic guidance in horses. Study design: Prospective experimental pilot cadaver study. Animals: Four equine cadavers of similar body weight (425-510 kg) and neck conformation. Methods: Five C7 and five C8 rami were perineurally injected with a dye solution. Anatomic dissections including vertebral canal opening were conducted to confirm nerve dye staining and describe the extent of color diffusion. Results: The ramus ventralis of the spinal cervical nerves was visualized in all cadavers. All the injections were successful in staining a portion of the nerve trunk. Eight rami had a uniform transversal staining of the nerve trunk that longitudinally covered a distance greater than 2 cm. One C7 and one C8 nerve trunk showed incomplete transversal staining with a more concentrated color on its half cranial aspect and a longitudinal coverage of less than 2 cm. Five injections resulted in dye extending proximally and medially into the epidural space. Volume had no appreciable effect on the extent of nerve staining. A greater proportion of epidural diffusion was found with injections done within less than one cm distally to the articular processes. All injections were considered to be selective for the targeted nerve. Conclusion and clinical relevance: Ultrasonography-guided perineural injection of C7 and C8 ramus ventralis is a feasible technique that may have multiple applications in multimodal analgesia in horses. Further clinical study will be necessary to determine the appropriate drug, dosage and volume to inject and to confirm its usefulness.